2019
DOI: 10.15507/1991-9468.094.023.201901.008-022
|View full text |Cite
|
Sign up to set email alerts
|

Using E-Learning Tools to Enhance Students- Mathematicians’ Competences in the Context of International Academic Mobility Programmes

Abstract: Introduction. The article is concerned with the use of special electronic teaching tools to increase the students’ understanding of the subject and adaptation to the professional language environment of the host country, taking into account the mathematical education. Our purpose is to develop a methodology of multilingual support of mathematical courses in the host country to improve the effectiveness of students’ academic mobility using e-learning tools. Materials and Methods. The basis of the research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…However, based on the questionnaire result on question number two, learners did not consider the applied teaching materials were excellent because 1) the explanation and the reading were not interesting, 2) the information and the examples were limited, and 3) there was no new information. The findings were in line with Andari & Sudarwati (2018), Snegurenko et al (2019), andWardani et al (2020) that teaching materials should be interesting and provide rich and meaningful information for learners. The interview results with learners, labeled AH, showed that he considered the examples were far from the reality they saw in real life (Interview result, 02/2021).…”
Section: Discussionsupporting
confidence: 88%
“…However, based on the questionnaire result on question number two, learners did not consider the applied teaching materials were excellent because 1) the explanation and the reading were not interesting, 2) the information and the examples were limited, and 3) there was no new information. The findings were in line with Andari & Sudarwati (2018), Snegurenko et al (2019), andWardani et al (2020) that teaching materials should be interesting and provide rich and meaningful information for learners. The interview results with learners, labeled AH, showed that he considered the examples were far from the reality they saw in real life (Interview result, 02/2021).…”
Section: Discussionsupporting
confidence: 88%
“…(Alzahrani, 2020).Estos hallazgos podrían influir en la creación de estrategias educativas para fomentar una mayor participación en el aprendizaje de matemáticas. También enfatizan la importancia de los recursos educativos en el desarrollo académico (Snegurenko et al, 2019). Así mismo, estos estudios destacan la importancia de abordar las barreras y desafíos en el uso de la tecnología en la educación, mientras se aprovechan los beneficios que ofrece para mejorar el aprendizaje y la enseñanza(T. Mailizar et al, 2020).…”
Section: Discussionunclassified
“…Students take part in learning systems and provide energetic reactions to math learning (Edo &Tasik, 2019;Rokhmah et al, 2019). In addition, mathematics is not just a tool to solve problems but must serve as an actual mindset formation and foster a positive attitude for vocational students to be able and adaptable (Effendi, 2017;Snegurenko et al, 2019;Sutama et al, 2015).…”
Section: Discussionmentioning
confidence: 99%